2019
DOI: 10.12659/aot.920086
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Early Urological Complications in Kidney Transplantation: A National Cohort Study

Abstract: BackgroundThis study aimed to provide an update on the occurrence of early urological complications in living-donor and deceased-donor kidney transplantation (KTX).Material/MethodsData on all kidney transplant recipients in the Netherlands between January 2005 and December 2015 were retrieved from the prospectively collected Dutch National Organ Transplant Registry Database (NOTR). We assessed the incidence of major urological complications (MUCs) within 3 months after KTX, defined as urinary leakage and urete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 22 publications
4
14
2
Order By: Relevance
“…In our analysis, UC occurred in 7% of cases after KT, mainly represented by urinary strictures. The UC rate of our population is in line with these reported by other recent studies [2,34]. Arpali E et al in 2018 described that UCs were observed in 9.3% of 2274 patients undergoing KT [2].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our analysis, UC occurred in 7% of cases after KT, mainly represented by urinary strictures. The UC rate of our population is in line with these reported by other recent studies [2,34]. Arpali E et al in 2018 described that UCs were observed in 9.3% of 2274 patients undergoing KT [2].…”
Section: Discussionsupporting
confidence: 92%
“…Arpali E et al in 2018 described that UCs were observed in 9.3% of 2274 patients undergoing KT [2]. Moreover, in 2019 a national registry study from the Netherlands reported that, among 3329 KT recipients, UCs were developed in 208 (6.2%) of patients within 3 months after surgery [34]. Compared to an older cohort [24,25,35,36], the reduced incidence of UC observed in the last decade could be related to many factors, but advances in surgical techniques have most probably had a major effect.…”
Section: Discussionmentioning
confidence: 99%
“…Many articles have referred to the incidence of urinary complications (1.0–9.2%) after kidney transplantation [ 17 21 ]. Common causes of urinary complications were vascularity of the donor ureter and the surgical technique.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Our findings are in concordance with those of van Roijen et al, who documented that surgical intervention of urological complications during the early post-operative period did not affect patient or graft survival. [11] It has been previously documented by Bruintjes et al [12] and Faenza et al [13] that there is no relationship between the type of urinary anastomosis and the risk for surgical urological complications. The success of ureterovesical anastomosis depends on the vascularity of the donor ureter, which may be compromised during the donor nephrectomy and by handling during transplantation.…”
Section: Discussionmentioning
confidence: 99%